Pelatihan Massage Efflurage dan Endorphin pada Pendamping Ibu Hamil di Wilayah Kerja Puskesmas Syamtalira Bayu Kabupaten Aceh Utara - Prihatin, Nova Sumaini; Jasmiati, Jasmiati; Rosyita, Rosyita; Erlina, Erlina (Jurnal Abdimas Kesehatan (JAK), 2025)
Physiological adaptation of the musculoskeletal system is one of the changes that pregnant women often complain about, especially in the third trimester of pregnancy, namely back pain which has long-term impacts that increase the tendency of postpartum back pain and the risk of suffering from venous thrombosis. Several complementary therapies to reduce back pain by doing effleurage and endorphin massage. Back pain can occur at any time so that a companion who can perform massage is needed. This community service activity aims to provide training in effleurage and endorphin massage to companions of pregnant women to reduce back pain during pregnancy in the Working Area of ​​the Syamtalira Bayu Community Health Center, North Aceh Regency. The target audience is 76 people, including 38 cadres as companions of pregnant women and 38 pregnant women in the third trimester who experience back pain during pregnancy in the Working Area of ​​the Syamtalira Bayu Community Health Center, North Aceh Regency. The implementation of the activity began with a pre-test to explore the knowledge of the target audience, then provided education about efforts to treat back pain and trained companions of pregnant women, namely cadres, about effleurage and endorphin messages. Evaluations were conducted two weeks after the training, using a Google Form to assess back pain after efflurage and endorphin massage, and to evaluate the skills of the cadres through videos sent during efflurage and endorphin massage sessions on pregnant women. The efflurage and endorphin massage training improved the knowledge and skills of the pregnant women's companions and effectively reduced pain levels. It is hoped that future community service providers can continue the training in other areas with regular evaluations and integrate the efflurage and endorphin massage training program into maternal health services for broader and more sustainable benefits